The significance of adopting the Islamic calendar in Islamic housing finance. Case study : Bank Muamalat Malaysia Berhad Parit Raja Branch - Dwidayati, Kunthi Herma (2016)
Malaysia is considered to be one of the most advance developed Muslim countries among Muslim countries that employ Islamic Banking system. In this context, Islamic Housing Finance has grown rapidly and becomes popular as a common solution for Muslims who desire to own home base on shariah principles. In Malaysia, banks which have Islamic Banking products employ Gregorian Calendar as the basis for their accounting system even though Surah At-Tawbah: 36-37 in Al-Quran has clearly depicted that there is a straight guidance for Muslims to use the Islamic Calendar for their mundane and spiritual lives. Factually, Gregorian Calendar is 11.5 days longer than the Islamic Calendar, thus using it will affect the calculation of loan repayment for every Muslim borrower. In previous research, discovered that Gregorian Calendar has caused the shortage of zakat payments by the Muslim customers, due to the shorter period of days calculated. This study was conducted to determine a reliable Islamic Calendar according hisab criteria (wujudul hilal) using Accurate Times. To identify the difference calculation between two calendars system and to calculate Islamic Housing Finance repayment in Islamic Calendar and Gregorian Calendar. Quantitative and Qualitative approach were employed in this research. Respondents are all customers at the Bank Muamalat Malaysia Berhad (Parit Raja) who chose Bai Bithamin Ajil (BBA) concept as their housing finance scheme. The calculation shows that total repayment in Islamic Calendar is lower than the Gregorian Calendar. Expert interview were used to identify the effect of employing Islamic Calendar in Islamic Banking system especially for Islamic Housing Finance. Finding indicates that the differences of total repayment between two calendar system reach average 1.04 per cent and most of the banks agree that Islamic Calendar can be employed as the basis of accounting system although many challenges appeared.